Early maladaptive schemas, cognitive fusion, and anabolic-androgenic steroid use attitudes: the mediating role of muscle dysmorphia in Iran - Ebrahimi, M.; Zamani, Z.; Bagheri, E. (Journal of Clinical Sport Psychology, 2024)
In recent decades, the interest in having an ideal body in men has caused a pathological tendency to be muscular, followed by a tendency to use anabolic-androgenic steroids (AASs). This study was designed to evaluate the mediating role of muscle dysmorphia in the relationship between early maladaptive schemas and body image-related cognitive fusion with the tendency to use AAS in male athletes. Out of the total number of men referring to fitness clubs in Isfahan, Iran, 474 men were evaluated using a multistage random cluster sampling method. The questionnaires used in this research included the Muscle Dysmorphic Disorder Inventory, Cognitive Fusion Questionnaire—Body Image, Young Schema Questionnaire—Short Form, and Prototype Willingness Model Questionnaire. The results demonstrated that the relationship of AAS use with body image-related cognitive fusion and the three maladaptive schemas with the mediation of muscle dysmorphia is significant. The present study provides significant implications in the discussion of prevention and treatment of AAS addiction.